# Subtraction of Mass | How to Subtract Mass between Different Units?

The subtraction of Mass is similar to the subtraction of numbers. The concept of borrowing is the same. If you are facing difficulty in solving the problems of subtraction of masses this web page will give detailed information on the concept. By completely going through this article you can also check solved examples of subtraction of mass. With this knowledge, you can solve subtraction of mass problems very easily.

### How to Solve Subtraction Problems Involving Mass?

When subtracting masses, we will learn how to find the difference between the units of mass or weight. If units of mass of both the minuend and subtrahend are in the same units then the difference is also in the same units. We can subtract the numbers like ordinary numbers.

If the minuend and subtrahend are in different units thenÂ we will learn two different models to solve subtraction of mass problems using the standard unit and smaller unit of mass. Both models can be practice by everyone.

(i)Â Subtracting units with conversion into gram

In this method, if the minuend and subtrahend are in different units i.e., kilogram and grams then they are converted into grams before subtraction and then follow the simple subtraction process.

(ii)Â Subtracting units without conversion into gram

In this method, we can subtract the units of mass like ordinary numbers without conversion of units of mass just by arranging the units in different columns and then subtracted like ordinary numbers.

### Subtraction of Kilograms and Grams Examples

Consider some examples of subtraction of mass. These examples are solved in both methods.

Example 1:

Subtract the weight of 18 kg 380 g from 29 kg 893 g

Solution:

Method 1Â (with conversion into gram):

As we know, 1 kg = 1000 grams

First, we have to convert, kg into g before doing subtraction and then we have to follow the simple subtraction process.

18 kg 380 g = (18 Ã— 1000) g + 380 g = 18000 g + 380 g = 18380 grams

29 kg 893 g = (29 Ã— 1000) g + 893 g = 29000 g + 893 g = 29893 grams

Now subtract,

2Â  9Â  Â 8Â  Â 9Â  Â 3 g

Â  1Â  Â 8Â  Â 3Â  Â 8Â  Â 0Â  Â  g
Â  Â  1Â  Â  1Â  Â 5Â  Â 1Â  Â 3Â  Â g

= 11 kg 513 g

Therefore, 29 kg 893 g – 18 kg 380 g = 11 kg 513 g

Method 2Â (without conversion into gram):

Arrange kg and gÂ  in different columns and then subtract like ordinary numbers.

(i) Arrange kg and gÂ  in columns and then subtract like ordinary numbers

(ii) 893 g – 380 g = 513 g

(iii) 29 kg – 18 kg = 11kg

Â  Â kgÂ Â Â Â Â Â Â  g
29Â  Â  Â 893

Â  18Â  Â  Â 380
Â  Â  11Â  Â  Â 513

= 11 kg 513 g

Therefore, difference of 29 kg 893 g from 18 kg 380 g = 11 kg 513 g

Example 2:

Subtract the weight 33 kg 755 g from 85 kg 678 g

Solution:

Method 1Â (with conversion into gram):

As we know, 1 kg = 1000 grams

First, kgs are converted into grams before doing subtraction and then we need to follow the simple subtraction process.

33 kg 755 g = (33 Ã— 1000) g + 755 g = 33000 g + 755 g = 33755 grams

85 kg 678 g = (85 Ã— 1000) g + 678 g = 85000 g + 678 g = 85678 grams

Now subtract,

8Â  5Â  Â 6Â  Â 7Â  Â 8 g

Â  Â 3Â  Â 3Â  Â 7Â  Â 5Â  Â 5Â  Â  g
Â  Â  5Â  Â  1Â  Â  9Â  Â 2Â  3Â  Â g

= 51 kg 923 g

Therefore, 85 kg 678 g – 33 kg 755 g = 51 kg 923 g

Method 2Â (without conversion into gram):

Here Arrange kg and gÂ  in different columns and then subtracted like ordinary numbers.

(i)Â  Arrange kg and g in columns

(ii) 678 g < 755 g, then 678 g – 755 g, so 1 kg from 85 kg is borrowed and added to 678 g

1 kg + 678 g = 1000 g + 678 g = 1678 g

1678 g – 755 g = 923 ml

(iii) 85 kg reduce into 84 kg

84 kg – 33 kg = 51kg

Â  Â kgÂ Â Â Â Â Â Â  g
85Â  Â  Â 678

Â  33Â  Â  Â 755
Â  Â  52Â  Â  Â 123

= 52 kg 123 g

Therefore, difference of 85 kg 678 g from 33 kg 755 g = 52 kg 123 g

Example 3:

Subtract the weightsÂ  25 kg 455 g from 39 kg 788 g without conversion into gram.

Solution:

Here Arrange kg and g areÂ  in different columns and then subtracted like ordinary numbers (without conversion into gram)

Â  Â kgÂ Â Â Â Â Â Â  g
39Â  Â  Â 788

25Â  Â  455
Â  14Â  Â  Â 333

= 14 kg 333 g

Therefore, the difference of 39 kg 788 g from 25 kg 455 g = 14 kg 333 g

Example 4:

Subtract the weights 66 kg 700 g from 139 kg 40 g with conversion.

Solution:

As we know, 1 kg = 1000 grams

Now converte kg into grams before doing subtraction and then we need to follow the simple subtraction process.

66 kg 700 g = (66 Ã— 1000) g + 700 g = 66000 g + 700 g = 66700 grams

139 kg 40 g = (139 Ã— 1000) g + 40 g = 139000 g + 40 g = 139040 grams

Now subtract,

1Â  Â 3Â  9Â  Â 0Â  Â 4Â  Â 0 g

Â  Â 6Â  Â 6Â  Â 7Â  Â 0Â  Â 0Â  Â  g
Â  Â  Â 7Â  Â 2Â  Â 3Â  Â 4Â  0Â  Â g

= 72 kg 340 g

Therefore, 139 kg 040 g – 66 kg 700 g = 72 kg 340 g

Example 5:

Subtract the weight 32 kg 119 g from 84 kg 180g using conversion method and without conversion.

Solution:

As we know, 1 kg = 1000 grams

Now convert kg into grams before doing subtraction and then we need to follow the simple subtraction process.

32 kg 119 g = (32 Ã— 1000) g + 119 g = 32000 g + 119 g = 32119 grams

84 kg 180 g = (84 Ã— 1000) g + 180 g = 84000 g +180 g = 84180 grams

Now subtract,

8Â  Â 4Â  Â 1Â  Â 8Â  Â 0 g

Â  Â 3Â  Â 2Â  Â 1Â  Â 1Â  Â 9Â  Â  g
Â  Â  5Â  Â 2Â  Â  0Â  Â 6Â  1Â  Â g

= 52 kg 061 g

Therefore, 84 kg 180 g – 32 kg 119 g = 52 kg 061 g

Method 2:

Here kg and g are arranged in different columns and then subtracted like ordinary numbers (without conversion into gram)

Â  Â kgÂ Â Â Â Â Â Â  g
84Â  Â  Â 180

Â  32Â  Â  119
Â  Â 52Â  Â  Â 061

= 52 kg 061 g

Therefore, the difference of 84 kg 180 g from 32 kg 119 g = 52 kg 061 g

Example 6:

Subtract the weight 48 kg 236 g from 99 kg 124 g

Solution:

Method 1Â (with conversion into gram):

As we know, 1 kg = 1000 grams

Now convert kgs into grams before doing subtraction and then we need to follow the simple subtraction process.

99 kg 124 g = (99 Ã— 1000) g + 124 g = 99000 g + 124 g = 99124 grams

48 kg 236 g = (48 Ã— 1000) g + 236 g = 48000 g + 236 g = 48236 grams

Now subtract,

9Â  Â 9Â  1Â  Â 2Â  Â 4 g

Â  Â  Â 4Â  Â 8Â  Â 2Â  Â 3Â  Â 6Â  Â  g
Â  Â  Â  5Â  Â  0Â  Â 8Â  Â 8Â  Â 8Â  Â  Â g

= 50 kg 888 g

Therefore, 99 kg 124 g – 48 kg 236 g = 50 kg 888 g

Method 2Â (without conversion into gram):

Here arrange kg and g in different columns and then subtracted like ordinary numbers.

(i) kg and g are arranged in columns

(ii) 124 g < 236 g, then 124 g – 236 g, so 1 kg from 99 kg is borrowed and added to 124 g

1 kg + 124g = 1000 g + 124 g = 1124 g

1124 g – 236 g = 888 ml

(iii) 99 kg reduce into 98 kg

98 kg – 48 kg = 50kg

Â  Â  kgÂ Â Â Â Â Â Â  g
9Â  9Â  Â  Â 1Â  Â 2Â  Â 4

Â  Â 4Â  8Â  Â  Â 2Â  Â 3Â  6

Â  Â  Â 5Â  0Â  Â  Â 8Â  8 8

= 50 kg 888 g

Therefore, difference of 99 kg 124 g from 48 kg 236 g = 50 kg 888 g

Example 7:

Subtract the weights of 20 kg 211 g from 69 kg 791 g

Solution:

Method 1Â (with conversion into gram):

As we know, 1 kg = 1000 grams

Now convert kg into grams before doing subtraction and then we have to follow the simple subtraction process.

20 kg 211 g = (20 Ã— 1000) g + 211 g = 20000 g + 211 g = 20211 grams

69 kg 791 g = (69 Ã— 1000) g + 791 g = 69000 g + 791 g = 69791 grams

Now subtract,

6Â  9Â  Â 7Â  Â 9Â  Â 1 g

Â  2Â  0Â  Â 2Â  Â 1Â  Â 1Â  Â  g
Â  Â  4Â  Â 9Â  Â 5Â  Â 8Â  Â 0Â  Â g

= 49 kg 580 g

Therefore, 69 kg 791 g – 20kg 211 g = 49 kg 580 g

Method 2Â (without conversion into gram):

Here arrange kg and g in different columns and then subtracted like ordinary numbers.

(i) kg and g are arranged in columns

(ii) 791 g – 211 g = 580 g

(iii) 69 kg – 20 kg = 49kg

kgÂ Â Â Â Â Â Â  g
6Â  9Â  Â  Â  Â 7Â  9Â  1

– 2Â  0Â  Â  Â  Â 2Â  1Â  Â 1Â Â
Â  Â 4Â  Â  9Â  Â  5Â  8Â  Â 0Â Â

= 49 kg 580 g

Therefore, difference of 69 kg 791 g from 20 kg 211 g = 49 kg 580 g

Scroll to Top
Scroll to Top